The Politics and Psychoanalysis of Comedy - Samuels, Robert (Lexington Books, 2023)
This book looks at the political aspects of comedy and how humor is shaped by unconscious social and psychological factors within a particular cultural and historical context. Updating Freud’s work on jokes, Robert Samuels argues that any universal model of comedy must take into account the role played by distinct genres, which are themselves determined by particular political psychopathologies. In looking at contemporary comedy, we encounter a structure that is often seen throughout the world: in response to what is experienced as a Leftist super-ego censoring thoughts and speech and a Libertarian Right which promotes free speech as the ultimate value. Within this dynamic, comedians seeking to make their audience laugh by poking fun at sensitive and taboo subjects, intentionally and unintentionally, these humorists present an alternative to Left-wing political correctness and identity politics. Contemporary comedians then cannot help but to cater to Right-wing politics since the Right is centered on loudly rejecting the cultural dictations of the Left.